ANALYTICAL THINKING SKILLS OF VOCATIONAL STUDENTS IN CIRCULAR MOTION CASES - Ikmah, Isti; Nugroho, Sunyoto Eko; Sutikno, Sutikno (Universitas Negeri Semarang, 2018)
Physics as a basic subject of engineering department in vocational school need to equip students with analytical thinking skills. The purpose of this study is to describe the analytical thinking skills of vocational students on engineering department in solving cases of circular motion, to describe the obstacle, and to describe the factors that influence. This research use mixed method with written test instrument, questionnaire and interview. The average value of students' analytical thinking skills is 50.65. Students have been able to identify the variables in the case of circular motion, but they can?t understand the relationship between each other variables in the cases of specific problems. Physics lesson is less integrated with the field of expertise so that students are poorly trained in applying the physics concept in the field of expertise. Obstacles and factors that affect students' analytical thinking skills are known to vary by category.